Vertically-integrated tropospheric moisture, energy and their fluxes over Bangladesh during landfall of tropical cyclones (MAUSAM, 1998)
The changes in the vertically-integrated tropospheric moisture. energy and their fluxes over Bangladesh have been studied during the landfall of three major cyclones at Bangladesh coast in the recent past. It has been found that the vertically- integrated tropospheric moisture, dry static energy, latent energy and total energy over the country have a tendency to decrease at the formation stages of the cyclones in the Bay of Bengal and then the same shows significant increase as the cyclones move northwards for ultimate landfall. The integrated zonal and meridional fluxes of moisture, dry static energy, latent energy and total energy exhibit significant changes both in magnitudes and signs during the northward movement of the cyclones.